Subjective and objective sleep quality in young women with posttraumatic stress disorder following sexual assault: a prospective study. Issue 1 (1st January 2021) - Yeh, Mary S. L.; Poyares, Dalva; Coimbra, Bruno Messina; Mello, Andrea Feijo; Tufik, Sergio; Mello, Marcelo Feijo
ABSTRACT: Background : Most posttraumatic stress disorder (PTSD) sleep disturbances reports have been conducted in male combat veteran populations, usually decades after the disorder's onset. Given the increase in the prevalence of violence against women and the fact that women are at greater risk for developing PTSD, it is critical to examine sleep abnormalities in this population. Objectives : To examine subjective and objective sleep quality in young women with PTSD following sexual assault compared with a control group at baseline and after one year of treatment. Methods : Seventy-four women with PTSD following sexual assault and 64 healthy controls with no history of sexual assault were assessed using the Clinician-Administered PTSD Scale (CAPS-5), the Beck Depression Inventory, the Beck Anxiety Inventory, the Pittsburgh Sleep Quality Index (PSQI), the Modified Fatigue Impact Scale, and the Insomnia Severity Index. Subjects also underwent full in-lab polysomnography. PTSD participants received pharmacological and/or psychological therapy between baseline and one-year follow-up. Results : The PTSD group had significantly higher scores in the clinical and sleep measurements than the control group. Although the PTSD group reported poorer subjective sleep quality than healthy controls, there were few between-group differences in objective sleep. Analysis of the PTSD group at baseline and one-year follow-up showed that the PSQI global score was a significant predictor of PTSD improvement. Conclusions : Sleep quality is impaired in young women with PTSD and may impact long-term treatment responses. Better sleep quality is significantly associated with PTSD improvement, independent of depression and anxiety. HIGHLIGHTS: Several variables may influence sleep abnormalities in PTSD patients, including the type of trauma, gender, age, and time elapsed since the trauma. The present study evaluates subjective and objective sleep assessments in young women with PTSD who had suffered sexual assault.